2003
DOI: 10.1073/pnas.1732912100
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer classification and prognosis based on gene expression profiles from a population-based study

Abstract: Comprehensive gene expression patterns generated from cDNA microarrays were correlated with detailed clinico-pathological characteristics and clinical outcome in an unselected group of 99 node-negative and node-positive breast cancer patients. Gene expression patterns were found to be strongly associated with estrogen receptor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

75
1,371
4
55

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,792 publications
(1,505 citation statements)
references
References 26 publications
75
1,371
4
55
Order By: Relevance
“…We have shown that FBC can be grouped in the different breast cancer subtypes described previously in SBC using IHC (Perou et al, 2000;Sorlie et al, 2001Sorlie et al, , 2003Sotiriou et al, 2003). In addition, we have performed a complete genomic characterization of the subtypes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We have shown that FBC can be grouped in the different breast cancer subtypes described previously in SBC using IHC (Perou et al, 2000;Sorlie et al, 2001Sorlie et al, , 2003Sotiriou et al, 2003). In addition, we have performed a complete genomic characterization of the subtypes.…”
Section: Discussionmentioning
confidence: 88%
“…A mixture of the three FBC groups was found in this subgroup (Figure 1). We termed these two subgroups as luminal A and B, respectively, according to the parameters (such as grade and differential expression of TOPOII) that have been used previously to discriminate between them (Sorlie et al, 2001;Sotiriou et al, 2003). Finally, a group of nine tumors were described (Figure 1, green branch), which had luminal features (positive for hormonal receptors and CK8), high grade and overexpression of CHEK2 and survivin.…”
Section: Unsupervised Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, gene expression profiling data have further refined the subtypes of breast carcinomas. [1][2][3][4]12 Among the five subgroups (luminal A, luminal B, normal breast-like, ERB2 þ and basal-like) of breast carcinoma identified by gene expression profiling, most attention has been given to basal-like carcinoma. The possible interest is due to the fact that these tumors were not well recognized before the expression profiling, but in retrospect they seem to have a relatively specific immunohistologic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that gene expression profiles are linked to ER status [3,4] and to clinical outcome [2,[5][6][7]. In metastatic breast cancer, a 44-gene expression signature was found to be associated with an objective response to tamoxifen [8].…”
Section: Introductionmentioning
confidence: 99%